The Procedure for Identifying the Compliance of the Performer’s Competencies with the Stated Requirements Based on The Bayesian Approach - V.Zaitseva, T.; V. Lomakin, V.; P. Putivtseva, N.; P. Pusnaya, O.; V. Ilyinskaya, E. (International Journal of Engineering and Technology, 2018)
The article proposes a procedure for the selection of personnel to perform specific activities based on a comparison of the general professional and professional competences obtained in the training process to the required level of qualification in order to effectively allocate labor resources. In this paper, a fragment of an example of the implementation of the procedure based on the use of professional standards for the large group 06.000 - Communication, information and communication technologies. The use of posterior probabilities calculated during the implementation of the procedure allows management personnel to make a decision on the selection of personnel with the most appropriate qualification for solving a particular task.
Keywords: professional standard; Bayesian theorem; competencies; labor functions; a priori probability; a posteriori probability